The Influence of Lifestyle, Consumptive Behavior and Brand Awareness on Used Clothing Purchase Decisions - Arsih Amalia Chandra Permata; Sudarmiatin, Sudarmiatin (CV. AFDIFAL MAJU BERKAH, 2024)
In the current era of globalization where the development of information between parts of the world is increasingly easily accessed through various media, whether through social media or online magazine media. Make it easier for everyone to access various kinds of existing information. Where the information presented is varied. Starting from food, lifestyle and so on. This incident emerged as a result of the development of popular culture in society, which was born from the will of the media (Adji & Clarretta, 2022). One of the impacts arising from popular culture is the emergence of the thrifting phenomenon among society. This research will discuss the influence of lifestyle, consumer behavior and brand awareness on purchasing behavior for thrifting goods. This research uses literature study techniques by applying the SLR (Systematic Literature Review) method or literature review method. The research results show that: 1) Lifestyle is proven to greatly influence the factors that determine whether or not to buy used clothes. 2) It has been proven that consumer behavior significantly influences the variables that influence the choice to buy used clothing. 3) It has been proven that brand awareness significantly influences the factors influencing the choice to buy used clothing. Lifestyle variables are proven to have a significant effect on variables Second-hand clothing purchase decisions. It is proven that the choice of buying used clothes is significantly influenced by variables Consumptive behavior, as well as the variable choice of buying used clothes are significantly influenced by Brand awareness variables based on several studies conducted